PEMANFAATAN DAGING TRIMMED DAN BELLY IKAN TODAK (Tylosurus crocodilus) PADA PEMBUATAN ABON IKAN - Tioko Arzeti Sinambela; R. Marwita Sari Putri; Azwin Apriandi (Marinade, 2020)
Fish floss is one of the traditional based products that are popular among the people of Indonesia. Fish floss is processed fish made from fish meat and traditionally processed through boiling, seasoning and frying/roasting. This study aims to produce the best formulation in the manufacture of trimmed meat based shredded fish and hound needlefish belly, to find out the level of preference for swordfish shredded products. The best hedonictest results are A4 formulation with a concentration of 35% belly and 15% trimmed giving an average value of appearance (3.40) aroma (3.43) taste (3.27) texture (3.5). The results of the proximate analysis based on the best treatment obtained values ​​of water content (15.27), ash content (8.16), fat content (19.34), and protein content (32.28). The highest essential amino acid test results obtained lysine value (2.68±0,007) while the highest non-essential amino acid analysis results obtained glutamic acid values ​​(4.82±0,028). The results of the analysis of the metal content of Pb and Hg shredded fish with an average value of (0.1 mg / kg) and the results of the analysis of Hg with an average value of (0.18 mg / kg)